Streptococcus oralis MitraClip endocarditis following a dental procedure: a case report - Aikaterini Papamanoli (BMC Infectious Diseases, 2021)
Abstract Background Transcatheter edge-to-edge mitral valve repair using the MitraClip device is increasingly used for high surgical risk patients with severe mitral regurgitation (MR). Previous guidelines for infective endocarditis prophylaxis prior to dental procedures focused on high-risk patients, but without explicit recommendation for MitraClip recipients. We believe this could be the first reported case to identify Streptococcus oralis as the causative organism. Case presentation An 87-year-old male with severe MR treated with two MitraClip devices three months prior to index admission, presented with worsening malaise and intermittent chills on a background of multiple comorbid conditions. The patient had dental work a month prior to presentation, including a root canal procedure, without antibiotic prophylaxis. Vitals were significant for fever and hypotension. On physical examination, there was a holosystolic murmur at the apex radiating to the axilla, bilateral pitting edema in the lower extremities, and elevated jugular venous pulsation. A transthoracic echocardiogram showed severe MR with a possible echodensity on the mitral valve, prompting a transesophageal echocardiogram, which demonstrated a pedunculated, mobile mass on the posterior leaflet of the mitral valve. Five blood cultures grew gram positive cocci in pairs and chains, later identified as Streptococcus oralis, with minimum inhibitory concentration to penicillin 0.06 mg/L. Initial empiric antibiotics were switched to ceftriaxone 2 gr daily and subsequent blood cultures remained negative. However, the patient developed pulmonary edema and worsening hemodynamic instability requiring vasopressors. As surgical risk for re-operation was considered prohibitive, the decision was made to continue medical management and comfort-directed care. The patient died a week later. Conclusions Despite low incidence, infective endocarditis should be included in the differential among MitraClip recipients. The explicit inclusion of this growing patient population in the group requiring prophylaxis prior to dental procedures in the 2020 ACC/AHA valvular heart disease guidelines is an important step forward.